Formação inicial do professor que ensina matemática nos anos iniciais no curso de pedagogia EAD - Konzen, Tanira Eloisa (2022)
The present research was developed in the Post-Graduate Program in Mathematics Education and Physics Teaching at the Federal University of Santa Maria – UFSM and has as theme training of teachers who teach mathematics. In this sense, the guiding question is: in what way does the teacher training process take place in the early years of the distance learning pedagogy course? The general objective of the research is to investigate aspects related to the training process of the future teacher who will teach Mathematics in the Distance Learning Pedagogy Course at UFSM. Therefore, the theoretical framework is divided into two chapters, which initially address the history of distance learning, the legislation that guarantees this type of education. the structure of the Distance Learning Pedagogy Course at UFSM, as well as the syllabus of Mathematics Education I and II subjects. The other chapter that brings theoretical basis refers to the initial training of teachers who will teach Mathematics in the early years. For this, we used different authors and their perceptions on the subject. To achieve our objective, we present the research scenario, defining our subjects who are academic students from Cerro Largo’s pole and who have already taken Mathematics Education I and II subjects, in addition to the tutors of these curricular components. As methodological actions, a questionnaire was developed with the students via Google Forms and another with Mathematics Education’s tutors. As main results, it was identified the little approximation of academic students with Mathematics, especially when they were Basic Education academic students. However, after studying the subjects mentioned above, future pedagogues feel prepared to teach Mathematics.